Climb High: Sondheim at the gateway to his career. Issue 2 (1st June 2019) - McHugh, Dominic
Sondheim has long identified his mentor, Oscar Hammerstein II, as one of the most influential figures in his life, both personally and creatively. In one interview, he called Hammerstein 'a surrogate father' and disclosed that '[h]e taught me how to structure a song, what a character was, what a scene was; he taught me how to tell a story, how not to tell a story, how to make stage directions practical'. The vehicle for this training was a four-part project: Hammerstein challenged the young Sondheim to write four musicals with specific criteria. The first three of these were abandoned before completion but Sondheim wrote a full script, music and lyrics for Climb High, working on the project from 1950 to 1953 with the obvious hope of having Hammerstein produce it on the stage (a frustrated ambition). Yet very little has been written about the work and Sondheim himself has been at pains to downplay its importance in his overall output. In this article, I exploit archival documents from Sondheim's papers at Madison, Wisconsin to shed new light on the process of writing the piece, as well as its many anticipations of Sondheim's mature work. In this way, I will place Climb High in the context of Sondheim's creative development: a flawed but fascinating document of a writer at the gateway to his professional career.